Flotillin-1 is an evolutionary-conserved memory-related protein up-regulated in implicit and explicit learning paradigms. (June 2013) - Monje, Francisco J.; Divisch, Isabella; Demit, Marvie; Lubec, Gert; Pollak, Daniela D.
Abstract Introduction. Studies of synaptic plasticity using the marine mollusk Aplysia californica as model system have been successfully used to identify proteins involved in learning and memory. The importance of molecular elements regulated by the learning- related neurotransmitter serotonin in Aplysia can then be explored in rodent models and finally tested for their relevance for human physiology and pathology. Materials and methods. Herein, 2-DE gel-based electrophoresis has been used to investigate protein level changes after treatment with serotonin in Aplysia abdominal ganglia. Results. Twenty-one proteins have been found to be regulated by serotonin, and protein level changes of actin depolymerizing factor (ADF), deleted in azoospermia associated protein (DAZAP-1), and Flotillin-1 have been verified by Western blotting. Discussion. Flotillin-1, a member of the flotillin/reggie family of scaffolding proteins, has been previously found to be involved in neuritic branching and synapse formation in hippocampal neurons in vitro. However, its importance for hippocampal- dependent learning and memory in the mouse has not been examined. Here, elevated levels of Flotillin-1 in hippocampal tissue of mice trained in the Morris water maze confirmed the relevance of Flotillin-1 for memory-related processes in a mammalian system. Thus, a translational approach—from invertebrates to rodents—led to the identification of Flotillin-1 as evolutionary-conserved memory-related protein.